Sprouty-related proteins with EVH1 domain (SPRED2) prevents high-glucose induced endothelial–mesenchymal transition and endothelial injury by suppressing MAPK activation. Issue 5 (2nd May 2022) - Liu, Tian; Zhao, Jing; Lin, Chengmin
ABSTRACT: Diabetic retinopathy (DR) is a common complication of diabetes, and the leading cause of blindness in adults. Sprouty-related proteins with EVH1 domain (SPRED2) play an important role in diabetes and are closely related to the lens and eye morphogenesis. This study attempted to investigate the role and related mechanism of SPRED2 in DR. DR rat model was established by administration streptozocin. Human retinal endothelial cells (HRECs) were treated with high glucose (HG) to mimic DR. The results showed that SPRED2 expression was decreased in the retinal tissues of DR rats and HG-treated HRECs. MTT assay and flow cytometry data showed that SPRED2 overexpression reduced cell viability of HG-treated HRECs. SPRED2 overexpression enhanced Caspase-3 activity and promoted apoptosis of HG-treated HRECs. Furthermore, the expressions of endothelial cell markers CD31 and E-cad were down-regulated, whereas the expressions of mesenchymal cell markers FSP1, SM22, and α-SMA were up-regulated in the HG-treated HRECs. SPRED2 overexpression reversed HG-induced endothelial–mesenchymal transition in HRECs. The expressions of tight junction components claudin 3, occludin, and ZO-1 were increased in HG-treated HRECs following SPRED2 up-regulation. In addition, SPRED2 overexpression downregulated the expression of p-ERK1/2, p-p38, and p-JNK in the HG-treated HRECs. In conclusion, this study demonstrated that SPRED2 overexpression repressed endothelial–mesenchymal transition and endothelial injury in HG-treated HRECs by suppressing MAPK signaling pathway. These findings suggested that SPRED2 may be a novel potential therapeutic target implicated in DR progression. Graphical abstract: uf0001